Low-temperature in situ growth of graphene on metallic substrates and its application in anticorrosion - Zhu, Minmin (2018)
Metal or alloy corrosion brings about huge economic cost annually, which is becoming one area of growing concern in various industries, being in bulk state or nanoscale range. Here, single layer or few layers of graphene are deposited on various metallic substrates directly at a low temperature down to 400 °C. These substrates can be varied from hundreds-micrometer bulk metallic or alloy foils to tens of nanometer nanofibers (NFs). Corrosion analysis reveals that both graphene-grown steel sheets and NFs have reduced the corrosion rate of up to ten times lower than that of their bare corresponding counterparts. Moreover, such low-temperature in situ growth of graphene demonstrates stable and long-lasting anticorrosion after long-term immersion. This new class of graphene coated nanomaterials shows high potentials in anticorrosion applications for submarines, oil tankers/pipelines, and ruggedized electronics.